Mask-Wearing Behavior towards COVID-19 Prevention - Erni Yetti Riman; Zadrak Tombeg; Anto J Hadi; Haslinah Ahmad; Fahrizal Alwi (Universitas Aisyah Pringsewu, 2023)
COVID-19 is an infectious disease caused by a coronavirus that occurs in the digitalization era and has become a global pandemic that can attack various age groups and hinder various types of activities. This study was to analyze the relationship between the behavior of wearing masks and the prevention of COVID-19. This study was a quantitative correlation with a cross-sectional design approach. 58 were applied and selected using accidental sampling. Data were collected using a questionnaire and analyzed using the chi-square and logistic regression. The results showed that knowledge (p=0.003), attitude (p=0.and 001), duration of eating at food stalls (p=0.021), personal protective equipment (p=0.041), health checks (p=0.041), behavior using masks (p=0.003) associated with the prevention of COVID-19, and of the four variables the most related is knowledge with a value of Exp (B)=11.466, p=0.033. The conclusion was obtained that the behavior of using masks is related to the prevention of COVID-19. It is hoped that the use of masks by health workers and the public in a disciplined manner during activities in public facilities or crowded places must be followed by other actions such as maintaining distance in crowded places and diligently washing hands with antiseptic soap to reduce the rate of spread and prevent transmission of the deadly virus. Abstrak: COVID-19 merupakan penyakit menular yang disebabkan oleh virus corona yang terjadi di era digitalisasi dan telah menjadi pandemi global yang dapat menyerang berbagai kelompok umur dan menghambat berbagai jenis aktivitas. Penelitian ini untuk menganalisis hubungan antara perilaku memakai masker dengan pencegahan COVID-19. Penelitian ini bersifat kuantitatif korelasional dengan pendekatan desain cross sectional. 58 diterapkan dan dipilih menggunakan sampling aksidental. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis menggunakan chi-square dan regresi logistik. Hasil penelitian menunjukkan pengetahuan (p=0.003), sikap (p=0.dan 001), lama makan di warung makan (p=0.021), alat pelindung diri (p=0.041), pemeriksaan kesehatan (p=0.041), perilaku menggunakan masker (p=0,003) berhubungan dengan pencegahan COVID-19, dan dari keempat variabel yang paling berhubungan adalah pengetahuan dengan nilai Exp (B) = 11,466, p = 0,033. Didapatkan kesimpulan bahwa perilaku penggunaan masker berhubungan dengan pencegahan COVID-19. Diharapkan penggunaan masker oleh tenaga kesehatan dan masyarakat secara disiplin saat beraktivitas di fasilitas umum atau tempat keramaian harus diikuti dengan tindakan lain seperti menjaga jarak di tempat keramaian dan rajin mencuci tangan dengan sabun antiseptik sehingga dapat mengurangi laju penyebaran dan mencegah penularan virus mematikan tersebut.